Prevention on enzymatic browning of banana juice by natural anti – browning agent / Nur Syazwani Mohd Nasarodin - Mohd Nasarodin, Nur Syazwani (2017)
Browning that occurs in fruits causes the nutritional value and product quality of fruit juices declines due to oxidation of polyphenol compounds that triggers the generation of brown, red or black pigments. The development of natural anti – browning agent has increased due to growing number of consumers that interest in fresh, natural and organic products. Onion has been reported to be a potent natural anti – browning agent. The effects of the onion extract on polyphenol oxidase enzyme in banana juice were investigated. PPO assay was determined by treated the banana juice with heated onion extract at concentration of 1.0, 2.5, 3.5 and 5.0 μg/ml. Addition of 5 μg/ml onion extract, gave the greatest inhibitory effect, 65.276 ± 0.620 % on banana polyphenol oxidase activity. The total phenolic content (TPC) was measured by Folin Ciocalteu reagent method and Gallic acid used as standard. TPC varied from 5.265 ± 0.009 mg GAE / 100 ml for treatment with highest heated onion extract to 5.613 ± 0.001 mg GAE / 100 ml for treatment with lowest heated onion extract. The inhibitory effect of polyphenol oxidase enzyme of banana juice by onion extract was increased with the increasing of concentration and time. Banana juices that treated with heated onion extract showed reduce browning as well as increased total phenolic concentration. Thus, it can be conclude that addition of onion extract may greatly inhibit browning and improve quality of banana juice.